Critical Race Theory and Hmong American Education - Christin DePouw (Hmong Studies Journal, 2018)
Critical race theory (CRT) in education provides important conceptual tools in analyses of Hmong American education. CRT in education centers race and racism in relation to other axes of oppression, thereby locating educational inequities that Hmong American youth experience within appropriate historical, social, and institutional contexts. These contexts support deeper analyses that consider the sociopolitical and intersectional factors that affect Hmong American youth and their families. Importantly, these analyses provide Hmong American students with the concepts needed to name and validate their experiences as part of the development of critical race consciousness.